The role of container security in application development - Morić, Zlatan; Redžepagić, Jasmin; Bencarić, Ivan; Dakić, Vedran (Edelweiss Applied Science and Technology, 2025)
This paper explores the importance of container security in modern ap-plication development, particularly in environments using microservices architectures and DevOps practices. Containers, by providing lightweight and portable virtualization, have transformed application deployment, enabling rapid and consistent transitions across development, testing, and production stages. However, their architecture and ease of use introduced unique vulnerabilities. This paper investigates the implications of these security concerns and outlines best practices to mitigate them. Examining containerization fundamentals, the paper identifies core vulnerabilities, including misconfigurations, runtime attacks, and orchestration layer risks. Techniques like namespace isolation, resource allocation controls, and security tools are evaluated for their effectiveness in hardening con-tainerized environments. Advanced methods, such as role-based access control, vulnerability scanning, and secrets management, are emphasized for securing CI/CD pipelines. The findings underscore the necessity of integrating robust security measures throughout the container lifecycle to protect sensitive data and maintain application integrity. By adopting a comprehensive container security strategy, organizations can balance the scalability and agility of containers and maintain the reliability and safety of their deployment infrastructure.